Comparative Legal Analysis of Electronic Services Provided by Government Agencies to Citizens and Legal Entities - Kuldysheva, Gulsara; Paraidin uulu, Shailoobek; Pazylov, Niiazbek; Bakirova, Shyrmanhan; Omorova, Gulzat (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of the study was to analyse the regulatory framework governing the provision of e-services in Finland, Estonia, the United States of America and the Kyrgyz Republic. [Methodology/approach/design] The quality of e-service provision in the countries was compared based on the Network Readiness Index (NRI) of 2023, in which the United States was ranked 1, Finland – 4, and Estonia and the Kyrgyz Republic – 22 and 94, respectively. [Findings] It was found that the widespread adoption of e-services is one of the key factors contributing to a country's economic development, as it enhances management efficiency and attracts both investors and specialists. However, such adoption depends significantly on government involvement, particularly through financial support for digital initiatives and the establishment of a robust legal and regulatory environment. The analysis reveals that Estonia, Finland, and the United States are actively working toward creating universal regulatory standards to ensure the quality, accessibility, and security of e-services. In contrast, the Kyrgyz Republic lacks a sufficiently modern and comprehensive legal infrastructure, which hinders the effective regulation and development of electronic services. [Practical implications] Therefore, it was recommended to increase state support for e-services by increasing funding for this sector and revising the current legislation taking into account the successful experience of other countries in Europe and around the world. It was suggested to implement the proposed transformations using the Kurt Lewin model.